Experimental study on supersonic film cooling on the surface of a blunt body in hypersonic flow - 付佳 易仕和 王小虎 何霖 葛勇 (Chinese physics B, 2014)
The experimental study focuses on the heat flux on a double cone blunt body in the presence of tangential-slot super- sonic injection into hypersonic flow. The tests are conducted in a contoured axisymmetric nozzle with Mach numbers of 7.3 and 8.1, and the total temperature is about 900 K. The injection Mach number is 3.2, and total temperature is 300 K. A constant voltage circuit is developed to supply the temperature detectors instead of the normally used constant current circuit. The schlieren photographs are presented additionally to visualize the flow and help analyze the pressure relationship between the cooling flow and the main flow. The dependence of the film-cooling effectiveness on flow parameters, i.e. the blow ratio, the convective Mach number, and the attack angle, is determined. A semi-empirical formula is tested by the present data, and is improved for a better correlation.